2009
DOI: 10.3892/ijo_00000426
|View full text |Cite
|
Sign up to set email alerts
|

The microtubule-associated protein MAPRE2 is involved in perineural invasion of pancreatic cancer cells

Abstract: Abstract. Perineural invasion of tumor cells is a characteristic feature of human pancreatic cancer. Unrevealing the molecular mechanisms that enable cancer cells to invade and grow along nerves is important for the development of novel therapeutic strategies in this disease. We have previously identified transcriptional changes in highly nerve invasive pancreatic cancer cells. Here we further analyzed one of the identified deregulated genes, MAPRE2, a microtubule-associated protein.MAPRE2 expression was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has been reported that MAPRE2 is overexpressed in hepatocellular carcinoma (35) and esophageal squamous cell carcinoma (36); thus, MAPRE2 might be involved in tumorigenesis and promotion of tumor cell growth through Wnt signaling pathway or Aurora-B activation (37,38). A study by Abiatari et al (39) demonstrated that overexpression of MAPRE2 is associated with decreased survival and perineural infiltration in pancreatic cancer patients. Therefore, MAPRE2 overexpression in various malignant tumors is positively correlated with tumor growth, nerve infiltration, and poor prognosis.…”
Section: Figure 6 |mentioning
confidence: 99%
“…It has been reported that MAPRE2 is overexpressed in hepatocellular carcinoma (35) and esophageal squamous cell carcinoma (36); thus, MAPRE2 might be involved in tumorigenesis and promotion of tumor cell growth through Wnt signaling pathway or Aurora-B activation (37,38). A study by Abiatari et al (39) demonstrated that overexpression of MAPRE2 is associated with decreased survival and perineural infiltration in pancreatic cancer patients. Therefore, MAPRE2 overexpression in various malignant tumors is positively correlated with tumor growth, nerve infiltration, and poor prognosis.…”
Section: Figure 6 |mentioning
confidence: 99%
“…Interestingly, we also found that the expression level of EB2 in SLHCC was lower than that in NHCC, which is consistent with our previous studies demonstrating distinct molecular characteristics between SLHCC and NHCC [21,[37][38][39], implying the potential of EB2 to determine the malignant behaviors and to distinguish different subtypes of HCC. Though EB2 was previously reported to be markedly up-regulated in highly nerve invasive pancreatic cancer cells [40], its biological function in cancer is still poorly defined. Here, we revealed that overexpression of EB2 significantly promoted HCC cell proliferation, invasion and metastasis in vitro and in vivo, whereas knockdown of EB2 inhibited these processes.…”
Section: Src Kinase Is Responsible For Eb2-mediated Erk Activationmentioning
confidence: 99%